Evaluation of porous concrete resistance to freezing by different methods/Akytojo betono atsparumo šalčiui, taikant skirtingas bandymų metodikas, vertinimas - Mačiulaitis, Romualdas; Nagrockienė, Dzigita (Journal of Civil Engineering and Management, 2001)
The article presents results of the comparative investigations into porous concrete specimens resistance to freezing (one-sided and volumetric). It has been determined that there is not any linear relation between the results obtained when calculating both the beginning of specimens disintegration (R = 0,2161753) and their disintegration end (R = 0,2621269). Besides, the data are very scattered and any other mathematical model did not allow to find a stronger non-linear relation. In addition, the destruction of porous concrete was analysed by measuring the change of relative linear deformations of porous concrete specimens under service resistance to freezing. It has been found that positive linear deformations are characteristic of low service frost resistance porous concrete specimens both during the one-sided freezing and thawing. When these deformations after some cycles reach (1,2–1,7%), the specimen surface disintegrates. Negative linear deformations are characteristic of specimens of high service frost resistance during one-sided freezing and thawing. The specimens of average service frost resistance (successfully resisted 25–30 cycles) can be characterised by the development of positive relative deformations during freezing and thawing. The processes have been investigated in detail taking place in identical specimens when they are investigated under different heat draining methods (one-sided and volumetric). The difference of humidity migration and localisation in respect of the freezing method has been disclosed. Some conclusions have been deduced from the investigation.Article in Lithuanian.First Published Online: 30 Jul 2012